Relationship between age at menarche and exposure to sexual content in audio-visual media and other factors in Islamic junior high school girls - Tity Wulandari; Melda Deliana; Sri Sofyani; Siska Mayasari Lubis (Indonesian Pediatric Society, 2017)
Background In recent decades, girls have experienced menarche at earlier ages, which may have negative effects on health. Exposure to audio-visual media and other factors may influence the age at menarche, although past studies have produced inconsistent results. Objective To assess for relationships between the age at menarche and audio-visual media exposure, socio-economic status, nutritional status, physical activity, and psychosocial dysfunction in adolescent girls. Methods This cross-sectional study was conducted from August to October 2015 in students from two integrated Islamic junior high schools in Medan, North Sumatera. There were 216 students who met the inclusion criteria: aged 10-16 years and experienced menarche. They were asked to fill out questionnaires that had been previously validated, regarding their history of exposure to audio-visual media, physical activity, and psychosocial dysfunction. The data were analyzed by Chi-square and Fisher’s exact tests in order to assess for relationships between audio-visual media exposure and other potential factors with the age at menarche. Results Of 261 female students at the two schools, 216 had undergone menarche, with a mean age at menarche of 11.6 (SD 1.13) years. There was no significant relationship between age at menarche and audio-visual media exposure (P=0.68). Also, there were no significant relationships between factors such as socio-economic and psychosocial status with age at menarche (P=0.64 and P=0.28, respectively). However, there were significant relationships between earlier age at menarche and overweight/obese nutritional status (P=0.02) as well as low physical activity (P=0.01). Multivariate logistic regression analysis showed that low physical activity had the strongest influence on early menarche (RP=2.40; 95%CI 0.92 to 6.24). Conclusion Age at menarche is not significantly associated with sexual content of audio-visual media exposure. However, there were significant relationships between earlier age at menarche and obese/overweight nutritional status as well as low physical activity.